Redescription of the Philippine leafhopper genus Iposcopus Baker (Hemiptera: Cicadellidae: Idiocerinae) - Xue, Qingquan; Mckamey, Stuart H.; Zhang, Yalin (Zootaxa, 2017)
The Philippine leafhopper genus Iposcopus Baker is redescribed. The male and female genitalia of I. breviceps and I. distanti are described and illustrated for the first time.        Baker (1915) established the genus Iposcopus and included two new species, I. breviceps and I. distanti (the type species) from the Philippines. Previously, only the external morphology and color have been described, not the genitalia. Here we first give a more complete description of the species, including male and female genitalia.